(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The potential for injury or mortality because of collisions between animals and operating current energy turbines remains an important research question with consequences for management of proposed marine energy projects. During a 141-day deployment of a small-scale (1 m2) tidal turbine, a sensing package including optical cameras and imaging sonars was used to record near-field interactions between animals and the turbine. Over 1000 events were captured by the optical cameras, including several species of fish, at least two species of diving birds, and harbor seals. Both seals and fish were observed in the vicinity of the turbine while it was operational, and a range of behaviors were captured. Seals and fish were also observed while the turbine was stationary, although the observed behaviors were different. Diving birds were observed regularly, but only during daytime hours and when the turbine was stationary. In this work, we summarize trends in animal behavior with respect to tidal elevation, time of day, and turbine operational state and discuss specific observations of collisions (only observed for fish), evasion (fish and seals), avoidance, and attraction. Although the results focus primarily on the optical camera data because optical images better resolve near-field interactions with the rotor, co-temporal sonar data are used to provide additional context to the interactions. Based on our experiences and findings we also recommend approaches for future projects seeking to acquire, analyze, and report on similar data sets.